Immobilization of laccase on chitosan-clay composite beads to improve its catalytic efficiency to degrade industrial dyes. (December 2020) - Mehandia, Seema; Sharma, S.C.; Arya, Shailendra Kumar
Abstract: High cost and low operational stability are the most important key challenges associated with the potential use of laccase for industrial applications. One possible solution to overcome these challenges is the immobilization of laccase. In this study, partially purified laccase from Alcaligenes faecalis XFI strain was immobilized onto chitosan beads (CB) and chitosan-clay composite beads (CCB) and employed for decolorization of three different synthetic dyes. The immobilization of laccase on CCB resulted in 88.4 % of immobilization yield and 151 U/g activity, which is higher than that of CB i.e. 83.6 % and 140 U/g respectively. This enhancement attributed to the synergetic effect of both clay and chitosan and their better biocompatibility with the laccase. The improved density (1.1002 g/mL), surface area (165.34 m 2 /g), pore volume (0.920 cm 3 /g), and pore size (33.12 nm) of the CCB evidenced the successful modiﬁcation of chitosan matrix. The thermal stability, operational stability and reusability of the laccase immobilized on CCB was observed to be better than CB. The adsorption property of bentonite clay significantly enhanced the decolorization efficiency of laccase immobilized on CCB. The results indicate that laccase immobilized on CCB can be used for various industrial applications.